2022
DOI: 10.1111/ijcs.12852
|View full text |Cite
|
Sign up to set email alerts
|

The role of intangible attributes of luxury brands for signalling status: A systematic literature review

Abstract: Previously, signalling status had been primarily studied from the conspicuousness of luxury brands, including high prices and prominent designs. However, less attention has been directed toward other elements of brands that could be strategically managed in order to enable consumers signalling status. This study synthesizes the literature using a framework based on four intangible attributes of luxury brands: user profile, purchase usage, personality and values and heritage. The topics studied under each of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 164 publications
0
8
0
Order By: Relevance
“…Previous research has suggested that power can originate from sources such as control over others, possession of knowledge, or ownership of material that is desired by others such as luxury brands (French & Raven, 1959; Fuentes et al, 2023). The possession of status is also a source of acquiring power since it represents control over valuable resources (Ho et al, 2023).…”
Section: Power and Status‐seekingmentioning
confidence: 99%
“…Previous research has suggested that power can originate from sources such as control over others, possession of knowledge, or ownership of material that is desired by others such as luxury brands (French & Raven, 1959; Fuentes et al, 2023). The possession of status is also a source of acquiring power since it represents control over valuable resources (Ho et al, 2023).…”
Section: Power and Status‐seekingmentioning
confidence: 99%
“…Recent research has shown increased interest in the role of customers' emotions and experiences, leading to the need to deliver meaningful services (Ko et al, 2019). Therefore, attracting customers with delightful experiences is asserted as one of the main objectives in today's retail environment (Grewal et al, 2009; Verhoef et al, 2009), as well as a pivotal aspect of luxury retail management (Fuentes et al, 2023; Kauppinen‐Raisanen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Luxury goods are commodities that possess physical, social, and psychological values that signify status besides contributing to luxurious living (Fuentes et al, 2023;Kumar, 2023;Slaton & Hurst, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned phenomena raised various questions that need to be investigated. First, which sectors of the luxury industry This review stands out from recent literature reviews on luxury products, notably differing from studies such as the study conducted by Fuentes et al (2023) which delves into the roles of luxury products as a social process signaling status, and the study by Luna-Cortés et al (2022) which focuses more on the hospitality industry. This study is expected to make a dual contribution, offering perspectives from both bibliometric and systematic literature review angles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation